Optimising the Role of TB Program Managers at Puskesmas in Increasing Coverage of TB Preventive Therapy in Serang Regency by 2024 - Murnidar Waruwu; Fajar Saputra (Jurnal EduHealth, 2025)
Tuberculosis (TB) is still a public health challenge in Serang Regency, with the coverage of Tuberculosis Prevention Therapy (TPT) that has not reached the target. This study aims to analyze the challenges and strategies for optimizing the role of TB program managers in Community Health Centers in increasing TPT coverage. This study used a qualitative method with in-depth interviews with nine informants, consisting of TB program managers, health workers, and policy makers at the Serang Regency Health Office. The results of the study showed that limited human resources (HR), low public awareness, lack of cross-sector support, limited number of active TB cadres, and drug distribution constraints were the main obstacles in implementing the TPT program. Efforts that have been made include training health workers, utilizing technology in patient monitoring, and cross-sector coordination, but still need to be strengthened to be more optimal. It is necessary to increase the capacity of health workers across programs and cadres who are trained in TB, increase public education, optimize drug distribution, and more supportive regional policies to increase TPT coverage and accelerate TB elimination.